Exploring the Wisdom of the Sunnah or Hadith as a Guide to Islamic Law - Soleh, Soleh; Apriantoro, Muhamad Subhi; Al Hafidz, Muhammad (Ethica: International Journal of Humanities and Social Science Studies, 2024)
Sunnah is a good or bad habit that is followed, both before and after the Prophet Muhammad SAW, including his words, actions and approval. The Hadith is a record of the words, actions or approval of the Prophet Muhammad SAW which includes information about his life and teachings. Then the role in Islamic law is that the Sunnah and hadith are important sources of law that provide guidance for everyday life. The Sunnah also provides strength, explanation and establishes laws that have not been regulated in the Qur'an. There are controversies and solutions. There is a group that doubts or rejects the validity of hadith as the basis of sharia. Reasons for rejection include the belief that the Qur'an already includes everything that is necessary and the validity of the hadith is questionable. There are also those who continue to defend the Hadith. The ulama have scientifically responded to the rejection arguments, strictly classified the hadith, and explained the need for further explanation of the Qur'an through hadith or sunnah.